A general phase ambiguity suppression algorithm combining geometric constraints and temporal phase unwrapping - Wu, Haitao; Cao, Yiping; An, Haihua; Xu, Cai; Li, Hongmei; Li, Yang (Optics and laser technology, 2022)
•A general phase ambiguity suppression algorithm is proposed.•The proposed method can unwrap the phase with minimum artifact.•Inherit the advantages of the two phase unwrapping algorithms•The proposed method is applicable to all TPU methods In fringe projection profilometry, various sophisticated temporal phase unwrapping (TPU) methods are conceived to recover a continuous absolute phase map. However, phase ambiguity is a thorny problem that affects measurement accuracy, which is deeply troubled by researchers. Dealing with the challenge, a universal algorithm (G-TPU) uniting geometric constraints phase unwrapping (GCPU) and TPU is proposed to comb out the phase ambiguity. Firstly, The invalid phase map or continuous relative phase map is unwrapped by GCPU with the minimum artifact. Then the unwrapped phas map is divided into several object regions, and the effective phase range (EPR) and invalid phase range (IPR) of each object region are determined by the proposed edge determination and image filling algorithm. Finally, through the statistical analysis of the decoded codewords, the relative orders are added to each EPR and IPR, and the absolute phase map is obtained. The proposed method inherits the complementary advantages of absolute position determination and strong robustness in TPU and GCPU respectively. Since GCPU does not need additional fringe patterns, it can be perfectly integrated into all TPU methods. The experimental results demonstrate the success of the proposed method combining GCPU and TPU.